The beach - DiCaprio, Leonardo; Swinton, Tilda; Ledoyen, Virginie, 1976-; Canet, Guillaume; Carlyle, Robert, 1961-; Macdonald, Andrew, 1966-; Boyle, Danny; Garland, Alex, 1970-; Twentieth Century-Fox Film Corporation; Figment Films (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2000)
A young backpacker in Thailand searching for something different learns of the existence of an idyllic island which is not even on the map. Once he reaches the island, he discovers a secret commune of international drifters living off fish and pot. The man's arrival coincides with growing tension between factions, leading to the commune's violent demise.
"Special edition"--Cover.
Originally released as a motion picture in 2000.
Based on the book by Alex Garland.
Music by Angelo Badalamenti ; editor, Masahiro Hirakubo ; production designer, Andrew McAlpine ; cinematography, Darius Khondji.
Leonardo DiCaprio, Tilda Swinton, Virginie Ledoyen, Guillaume Canet and Robert Carlyle.
MPAA rating, R. Canadian home rating, 14A.
Keywords: Beaches -- Southeast Asia -- Drama; Southeast Asia -- Drama; Feature films; Films for the hearing impaired; Action and adventure films